(untitled) (American & British Studies Annual, 2024)
As American Literature began to depart from European models in the seventeenth and eighteenth centuries, Shakespeare came to be venerated with increasing enthusiasm, and was often regarded in quasi-religious terms, even as other British writers fell out of favor. This “Bardolatry” culminated in the late nineteenth century with the critical and appreciative writings of Robert Green Ingersoll, who was both the most prolific writer on Shakespeare and the most celebrated atheist and secularist of his age. Ingersoll’s appropriation of Shakespeare, as both a sceptic whose political and religious opinions reflected his own and an object of religious veneration to resemble and challenge the figure of Christ, exercised a strong influence on later writers, both popular and academic. This influence shaped the way in which Shakespeare is now widely regarded in America as the one indispensable secular writer and the center of a world canon.